A study of factors influencing the adoption of online groceries shopping among generation X in Klang valley - Cheong, Carine Ji Ling; Lee, Jia Ying (2018)
The main objective of the research is to study on factors influencing the adoption of online groceries shopping among Generation X in research is to study on the relationship between Klang Valley . However, this the independent variables, convenient, perceived ease of use, subjective norms, trust and the dependent variable, adoption of online groceries shopping among the Generation X. O ur target respondents of this research are the consumers of e factors Generation X who are having intention or who do not have intention to adopt online groceries shopping, and those who had or have not used online grocery shopping before and lastly to figure out th that will influence the consumers of Generation X to adopt the online groceries shopping in future. In addition, 200 questionnaires were distributing to the respondents through the online Google form and collected 200 responds from them. The data collected will be analysed by using the Statistical Package for Social Science (SPSS) and the Reliability Analysis test, Pearson’s Correlation Analysis and Multiple Regression Analysis will be conducted in this research. Based on the result on Multiple R egression Analysis, the result shows that the independent variables of convenience, subjective norms, and trust have the positive significant relationship with dependent variable of adoption of shopping. Therefore , the independent variable online groceries of perceived ease of use has no positive significant relationship with dependent variable of adoption of online groceries shopping. Moreover, this research provided a clearer overview for developers, academicians and users who are involving in the adopti on of using online groceries shopping. Lastly, limitations of this research were identified and the implications for further research were recommended in this research.